2011
DOI: 10.7326/0003-4819-154-12-201106210-00009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Thiopurine S-Methyltransferase Activity in Patients Prescribed Thiopurines: A Systematic Review

Abstract: Agency for Healthcare Research and Quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 86 publications
3
79
0
1
Order By: Relevance
“…In fact, thiopurine-related myelotoxicity can, at least partly, be predicted by TPMT genotyping [66,67]; however, other side effects, including fever, arthralgia, hepatitis, and pancreatitis, are independent of TPMT status in up to 70 % of patients [62,66]. To date, more than 35 variants of the TPMT gene have been associated with decreased enzymatic TPMT activity [68][69][70][71][72][73].…”
Section: Genotypingmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, thiopurine-related myelotoxicity can, at least partly, be predicted by TPMT genotyping [66,67]; however, other side effects, including fever, arthralgia, hepatitis, and pancreatitis, are independent of TPMT status in up to 70 % of patients [62,66]. To date, more than 35 variants of the TPMT gene have been associated with decreased enzymatic TPMT activity [68][69][70][71][72][73].…”
Section: Genotypingmentioning
confidence: 97%
“…Accordingly, TPMT testing prior to the initiation of thiopurine therapy has been acknowledged and recommended by several published guidelines to prevent myelotoxicity [55][56][57][58][59]. However, the European Crohn's and Colitis Organisation (ECCO) does not have this recommendation in its recent guidelines [60,61], and a comprehensive systematic review concluded that insufficient evidence exists that this strategy is effective in reducing harm or is superior to the well-established clinical standard of hematologic monitoring [62]. Thus, the clinical and economic benefits of these tests in practice still remain controversial.…”
Section: Thiopurine S-methyltransferase Testingmentioning
confidence: 98%
“…60 A meta-analysis by Booth et al for discriminating between patients with low or intermediate TPMT enzyme activity (homozygous or heterozygous TPMT mutations) and the rest of the population reported a sensitivity range of 70.33-86.15% (lower-bound 95% CI, 54.52-70.88%; upper-bound CI, 78.50-96.33% for phenotype tests and a pooled estimate of 79.90% (95% CI, 74.81-84.55%) for genotype tests. 61 Due to the rarity of the homozygous mutation, Booth et al did not meta-analyze tests discriminating between patients with deficient TPMT enzyme activity (homozygous TPMT mutation) and the rest of the population.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are research groups that do not advocate for TPMT genotyping before treatment with thiopurines (Booth et al, 2011). The Agency for Healthcare Research and Quality (AHRQ) concluded that ″there is currently insufficient evidence regarding the effectiveness of determining TPMT status prior to thiopurine treatment in terms of improvement in clinical outcomes and incident myelotoxicity in comparison with routine monitoring of full blood counts and adverse events″ (http://www.ahrq.gov/clinic/tp/tpmttp.htm#Report).…”
Section: Guidelines For Thiopurine Dosing Based On Tpmt Genotypementioning
confidence: 99%